2022
DOI: 10.1155/2022/3858122
|View full text |Cite
|
Sign up to set email alerts
|

Inertness of Superoxide Dismutase Mimics Mn(II) Complexes Based on an Open-Chain Ligand, Bioactivity, and Detection in Intestinal Epithelial Cells

Abstract: Oxidative stress is known to play a major role in the pathogenesis of inflammatory bowel diseases (IBDs), and, in particular, superoxide dismutase (SODs) defenses were shown to be weakened in patients suffering from IBDs. SOD mimics, also called SOD mimetics, as low-molecular-weight complexes reproducing the activity of SOD, constitute promising antioxidant catalytic metallodrugs in the context of IBDs. A Mn(II) complex SOD mimic (Mn1) based on an open-chain diaminoethane ligand exerting antioxidant and anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…To avoid this possible bias and to also determine the amount of intact metal complex in cells, we wanted to directly track it in cell lysates. We showed previously using LC/MS‐MS, [25] that Mn1 penetrates the cells but the fact that the m / z peak of [Mn1] + (408.1465) is very close to that of the m / z peak of [Fe1−H] + (408.1355), with overlapping isotopic patterns prevented any reliable quantitative analysis, as previously performed with a more inert analogue [69] . Recently, to investigate the Mn1 subcellular location, a multimodal Re‐tris carbonyl probe was conjugated to the ligand.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…To avoid this possible bias and to also determine the amount of intact metal complex in cells, we wanted to directly track it in cell lysates. We showed previously using LC/MS‐MS, [25] that Mn1 penetrates the cells but the fact that the m / z peak of [Mn1] + (408.1465) is very close to that of the m / z peak of [Fe1−H] + (408.1355), with overlapping isotopic patterns prevented any reliable quantitative analysis, as previously performed with a more inert analogue [69] . Recently, to investigate the Mn1 subcellular location, a multimodal Re‐tris carbonyl probe was conjugated to the ligand.…”
Section: Introductionmentioning
confidence: 93%
“…A comprehensive evaluation of high‐performance liquid chromatography‐mass spectrometry (HPLC‐MS) for a large‐scale study of metal complexes was reported elsewhere [68] . It has been also applied very recently to a more inert Mn‐based complex similar to Mn1 [69] . More labile compounds present additional problems, especially when they interact with the stationary phase and the tubing of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide dismutase mimetics are low-molecular-weight complexes that mimic the activity of superoxide dismutase [ 10 , 11 , 12 ]. Such compounds may present antioxidant and anti-inflammatory activity [ 13 , 14 , 15 , 16 ], and they have also been evaluated for their antitumoral activity [ 17 ]. SOD mimetics are proposed to lead to an increase in cellular H 2 O 2 , which induces antitumoral activity in vitro due to the difference in hydrogen peroxide cellular sensitivity between normal and cancer cells [ 3 , 6 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mn1 [ 31 ] is a MnSOD mimic bio inspired by the active site of MnSOD, specific of superoxide, [ 32 ] with better intracellular diffusion compared to mangafodipir [ 13 , 15 , 16 ]. It was shown to exert anti-inflammatory activity in a cellular model of inflammatory bowel diseases (HT29-MDM2) associated with an antioxidant effect [ 13 ].…”
Section: Introductionmentioning
confidence: 99%